(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
From a perspective located at a considerable distance from an admission without any problematics of the cultural program of the Dominican humanist Pedro Henríquez Ureña, we propose a critical reading of the theory of miscegenation as a source of harmony and sociocultural integration of Hispanic-America that threads a great amount of the author´s texts. Our working hypothesis tries to question the idea of Miscegenation, in which the autochthonous and Spanish elements interfere, and functions at the mercy of some strategic selections; for example, the clipping of an image of Spanish America at the expense of the Caribbean area and, consequently, of other existing ethnic reserves. On the other hand, we propose that the resource of the merger or miscegenation does not prove, at last, a sly way of eluding the conflict and cultural instability of the continent. Finally, we wish to consider the reasons for which he sticks fast and firmly to humanism as a suitable doctrine to set the course for an argumentation of harmony for these very different elements, without neglecting any positivists notes which might last in the allusions to race.